Influência da clareação dentária sobre o tecido pulpar de ratos diabéticos: aspectos histológicos e imunológicos - Ferreira, Luciana Louzada [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Objective: To evaluate the influence of dental bleaching on the pulp tissue of diabetic rats over the histological aspects and proinflammatory cytokines regulation. Methods: Twenty-eight Wistar rats were divided into four groups: (N) normoglycemic; (NBle) normoglycemic-bleached, (D) diabetic, (DBle) diabeticbleached. Fourteen animals reveiced a 150mg/kg dose of alloxan for diabetes induction, via IM. After 3 days, all animals were anesthetized and the dental bleaching performed using 35% hydrogen peroxide (H2O2) gel (Whiteness HP Maxx) in the right maxillary molars for 30 minutes. Left upper molars were used as control. Two and 30 days after the animals were euthanized, and the hemi-maxillae processed for histological and histochemistry analysis. Qualitative analyses were performed for inflammatory reaction and immunolabelling, and quantitative for pulp chamber area reduction and collagen fibers. The results were submitted to statistical analysis (p<0.05). Results: At two days a mild inflammation was observed in NBle group and severe for DCla (p<0.05). For the maturation of collagen fibers, at two days was observed an increase amount of immature fibers in the N group, with statistical difference to the other groups (p<0.05), and a reduced amount of mature fibers in the N group with significant diference to the other groups (p<0.05). At 30 days no inflammatory cells were observed and there was no statistical difference between the groups for both fibers type (p>0.05). However, there was a significant difference when NBle and DBle groups were compared with regards to reduction of the pulp chamber area due the presence of reactionary dentin deposition (p<0.05). With regards to immunoistochemistry, was observed for IL-6 at 2 days an increased immunolabelling in the bleached groups (NBle and DBle) (p<0.05)...

Objetivo: Avaliar a influência da clareação dentária sobre o tecido pulpar de ratos diabéticos por meio da observação dos aspectos histológicos e imunológicos. Material e Método: Vinte e oito ratos Wistar foram divididos em quatro grupos: (N) normoglicêmicos; (NCla) normoglicêmicos-clareados; (D) diabéticos; (DCla) diabéticos-clareados. Quatorze animais receberam uma dose de 150mg/kg de aloxano para indução da diabetes, via IM. Após 3 dias, todos os animais foram anestesiados e realizado o procedimento clareador com gel de peróxido de hidrogênio (H2O2) a 35% (Whiteness HP Maxx) aplicado uma vez nos molares superiores direitos por 30 minutos. Os molares superiores esquerdos foram usados como controle. Após 2 e 30 dias os animais foram eutanaziados e as maxilas processadas para análise histológica e histoquímica. Foram realizadas análises qualitativas para a reação inflamatória e imunomarcação, e quantitativas para a redução da área da camara pulpar e fibras colágenas. Os resultados foram submetidos à análise estatística com nível de significância de 5% (p<0.05). Resultados: Aos 2 dias observou-se infiltrado inflamatório leve no grupo NCla e severo no grupo DCla (p<0.05). Quanto ao grau de maturação das fibras colágenas, aos 2 dias observou-se maior quantidade de fibras imaturas no grupo N, com diferença estatística para os demais grupos (p<0.05), e, menor quantidade de fibras maduras no grupo N com diferença significante para os demais grupos (p<0.05). Aos 30 dias não foi observado concentração de células inflamatórias e não houve diferença estatística entre os grupos para ambas as fibras colágenas (p>0.05). Entretanto, houve diferença significante quando comparados os grupos NCla e DCla em relação à redução da área da câmara pulpar devido a deposição de dentina reacionária...
Keywords: Clareamento dental; Diabetes mellitus; Inflamação; Citocinas; Colágeno; Teeth bleaching